The final decision of the President of the Office of Competition and Consumer Protection in cases of practices infringing collective consumer interests as evidence in group proceedings in cases of ascertaining the application of practices infringing consumers’ general interests - Świeca, Karolina (The Opole Studies in Administration and Law, 2025)
The present study is an analysis of the research problem which is the possibility of giving preliminary ruling effect to final decisions of the President of the Office of Competition and Consumer Protection. The purpose of the article is to highlight doubts arising in the context of possible binding of the court to final decisions of the President of the Office of Competition and Consumer Protection in cases of practices that infringe the collective interests of consumers in group proceedings for ascertaining the application of practices that infringe consumers’ general interests or those of claims related to their application. The thesis that the decisions of the President of the Office of Competition and Consumer Protection should have the force of evidence and not the force of a preliminary ruling seems justified. However, regarding this aspect, there arises a research question concerningthe scope of assessments. The following research methods were applied: content analysis and systemic method. Group proceedings cover interests of collective consumers as well as interests of a group of individual consumers, in contrast to administrative proceedings conducted by the President of the Office of Competition and Consumer Protection. In addition, there is a possibility that the court may be bound by defective decisions, which would contradict the principle of legal certainty. The analysis is important because of its impact on shaping of the legislation on vindication of claims in court proceedings between consumers and traders.